(untitled) (Bangladesh Journal of Medical Science, 2023)
Background: Alfalfa extract has been shown to have anti-inflammatory activity in wound healing. Objectives: This study aims to investigate the effect of Alfafa on the number of macrophages, fibroblast, and collagen in the rat wound healing. Method: In this post-testonly control group design study, 50 Wistar rats were randomly divided into five groups. K0 (negative control) group was treated with ointment base. K1 (positive control) group was treated with gentamicin. P1, P2, and P3 groups were treated with 10%, 20%, and 30% alfalfa extract respectively. The termination of rats conducted on day 3 and day 7 post of first treatment (5 rats/group/period). On day 3, the number of macrophage and fibroblast were evaluated using Hematoxylin-Eosin staining. On day 7, the number of collagen was evaluated using Siriusred staining. The data were analyzed using one way ANOVA followed by Tukey’s post hoc test. Result: The result, showed a significant difference in the number of macrophages between the negative control treated group and K1 groups. The number of fibroblasts was significantly different between the P3 group and the P1, K1 group. There was a significant difference in the number of collagens between negative control andtreated group, and between the positive control and P2, P3 group. Conclusion: The administration of alfalfa extract at the dose of 20% can accelerate wound healing by increasing the number of fibroblasts and collagen fibers and decreasing number of macrophages. Bangladesh Journal of Medical Science Vol. 22 No. 01 January’23 Page : 77-83